Spontaneous focusing on numerosity and the arithmetic advantage. (December 2015) - Batchelor, Sophie; Inglis, Matthew; Gilmore, Camilla
Abstract: Children show individual differences in their tendency to focus on the numerical aspects of their environment. These individual differences in 'Spontaneous Focusing on Numerosity' (SFON) have been shown to predict both current numerical skills and later mathematics success. Here we investigated possible factors which may explain the positive relationship between SFON and symbolic number development. Children aged 4–5 years ( N = 130) completed a battery of tasks designed to assess SFON and a range of mathematical skills. Results showed that SFON was positively associated with children's symbolic numerical processing skills and their performance on a standardised test of arithmetic. Hierarchical regression analyses demonstrated that the relationship between SFON and symbolic mathematics achievement can be explained, in part, by individual differences in children's nonsymbolic numerical processing skills and their ability to map between nonsymbolic and symbolic representations of number. Highlights: Spontaneous focusing on numerosity (SFON) is linked to an arithmetic advantage. High-SFON children perform better than low-SFON children on an arithmetic task. We investigate the possible factors underpinning this advantage. It is partly due to fluency with nonsymbolic and symbolic number representations. SFON may lead to increased practice mapping between these representations.